Meso-Scale Modelling Of Pultruded Hybrid Composite Under Impact Loading - Omar, Mohammad Shafiq (Universiti Sains Malaysia, 2022)
Composite is one of the substances that, during the course of their life cycle, have been put through a range of mechanical stresses and been subjected to harsh climatic conditions. Genarally, there are three type composite in the industries which is natural composite, synthetic composite and hybrid composite. Kenaf/glass hybrid composite is the type of material which will be futher study in this project. Both naturally occurring fibres and manufactured fibres may be used to strengthen composite materials, each of which comes with their own set of benefits and drawbacks. In order to enhance the qualities of the composite material, the hybrid composite was developed and implemented. However, there has only been a very limited amount of research done on how hybrid natural composites behave when subjected to impact loading. The study about the composite was done by using Abaqus 2021 software which used to imitate the testing system that is widely used in the industries which is SHPB test. Several journal has been study to find out suitable parameter and setting to be used along the simulation process. before proceeding with simulation, the model of specimen was created by using Solidwoks 2019. Based on the finding from the simulation, stress propagation, stress distribution and failure mode occur in the simulation can be observed. Glass fiber is the component wear its bear most of the load which is come from the impact of the striker bar. The deformation of the fiber also can be seen at the edge of the matrix.